Differences in adult egg output of Schistocephalus solidus from singly- and multiply-infected sticklebacks - Dorucu, M.; Wilson, D.; Barber, I. (Allen Press Inc, 2007)
In this study, we recovered Schistocephalus solidus plerocercoids from singly and multiply infected three-spine sticklebacks, Gasterosteus aculeatus, transferred them individually to in vitro culture conditions, and quantified their lifetime egg output. We found a significant difference in the relationships between plerocercoid mass and lifetime egg output for parasites recovered from singly and multiply infected sticklebacks. Although egg output was strongly and positively related to plerocercoid mass amongst worms from singly infected fish, for those recovered from multiply infected sticklebacks the relationship was marginally nonsignificant and negative, with small worms achieving high levels of egg production. We suggest 2 hypotheses that may explain differences in the egg production of plerocercoids from singly and multiply infected fish. One possibility is that smaller plerocercoids in asymmetric multiple infections develop precocially, in response to host manipulation strategies of larger worms that decrease survival prospects of the host. Alternatively, small worms in singly infected sticklebacks may be prevented from becoming sexually mature because they face energetic constraints associated with having to overcome the host's immune response alone. We discuss our results in terms of recent studies examining strategic egg production in helminths.
Keywords: Gasterosteus-Aculeatus L; 3-Spined Stickleback; Intermediate Host; Hermaphroditic Cestode; Infectivity; Size; Time